Cataract after proton beam therapy (PBT) for iris melanoma - Coutinho, I (2015)
Introduction: Iris melanoma is a very rare tumour in paediatric age group. Treatment depends on, among other factors, tumour size and location, presence of any associated complication and general health of the patient. Management options include local resection, plaque brachytherapy, proton beam therapy (PBT) and enucleation. PBT is nowadays an alternative and effective treatment, with good local control, especially for extensive and diffuse tumours, in which local resection is difficult. The major complication is cataract and in paediatric age, surgery is always a challenge. Methods: A 8-year-old caucasian child, with blue iris, presented with a pigmented lesion in the inferotemporal iris of the left eye. It was interpreted as a nevus and documented by photography of the anterior segment and ultrasonic biomicroscopy in serial reassessments. Twelve months later, the lesion had grown in diameter and thickness associated with corectopia and ectropion uveae but did not involve the angle or ciliary body and intraocular pressure was normal. A diffuse iris melanoma was assumed and it was performed PBT. Results: The clinical evolution was favourable. Three years post PBT, we did not report any recurrence of the tumour neither evidence of metastatic disease. After 18-months, the patient developed a posterior subcapsular cataract in OS. The best correct visual acuity (BCVA) OS passed from 20/20 to light perception during 3 years. At age of 11, it was performed a micro-incision phacoemulsification cataract surgery combined with primary posterior capsulorexis, intracameral triamcinolone injection and implantation of a simple piece intraocular lens. No intra-operative complications were observed. BCVA was OS 20/20 after 9 months of follow up. Conclusion: We present a young boy with a diffuse iris melanoma treated with PBT. Primary PBT was well tolerated and the main complication was cataract, which was successful treatable, although in paediatric age is always a surgical challenge. Paediatric cataract surgery is a complex procedure with all aspects of the surgical process requiring care and attention. The use of micro-incision phacoemulsification with intracameral triamcinolone and posterior capsulorexis seems to provide significantly less anterior segment inflammation and no visual axis obscuration after cataract surgery with IOL implantation.